2012
DOI: 10.1371/journal.pone.0047838
|View full text |Cite
|
Sign up to set email alerts
|

Role of Disulfide Cross-Linking of Mutant SOD1 in the Formation of Inclusion-Body-Like Structures

Abstract: BackgroundPathologic aggregates of superoxide dismutase 1 (SOD1) harboring mutations linked to familial amyotrophic lateral sclerosis (fALS) have been shown to contain aberrant intermolecular disulfide cross-links. In prior studies, we observed that intermolecular bonding was not necessary in the formation of detergent- insoluble SOD1 complexes by mutant SOD1, but we were unable to assess whether this type of bonding may be important for pathologic inclusion formation. In the present study, we visually assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…9, which also shows how the Trx and GSH-Grx systems participate in this process. Mutation in hSOD1 dimers exposes its conserved Cys 57 -Cys 146 disulfide on the protein surface in either one or both subunits (28,29), where it is easy to be reduced by the Trx and Grx systems into dithiol form, followed by the dimer dissociation. We can also find non-conserved disulfide bond forms, as Cys 6 -Cys 111 and Cys 146 -Cys 111 in SOD1 dimers, that are in a balance because of the Trx-GSH/ Grx redox systems.…”
Section: Discussionmentioning
confidence: 99%
“…9, which also shows how the Trx and GSH-Grx systems participate in this process. Mutation in hSOD1 dimers exposes its conserved Cys 57 -Cys 146 disulfide on the protein surface in either one or both subunits (28,29), where it is easy to be reduced by the Trx and Grx systems into dithiol form, followed by the dimer dissociation. We can also find non-conserved disulfide bond forms, as Cys 6 -Cys 111 and Cys 146 -Cys 111 in SOD1 dimers, that are in a balance because of the Trx-GSH/ Grx redox systems.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that in hSOD1 G93A, Cys-111 becomes more sensitive to redox modifications, probably because of increased solvent accessibility. This increased exposure to the solvent may lead to intermolecular thiol/disulfide exchange reactions and aggregation (15,26,38). It is also possible that structural perturbations caused by the mutation result in decreased reactivity of Cys-111 (54) (53).…”
Section: Discussionmentioning
confidence: 99%
“…Formation of insoluble aggregates containing SOD1 is a common pathophysiological characteristic of ALS (6,11). Non-native disulfide formation contributes to form and/or stabilize SOD1 aggregates that accompany progression of the disease (12)(13)(14)(15). Indeed, it has been suggested that scrambling of the disulfide and the free cysteines in SOD1 results in formation of insoluble aggregates (16).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
See 1 more Smart Citation
“…The final interface is extended for about 1900 Å 2 , composed of 114 residues participating in the contact through 432 atoms and, as observed for the dimer of dimers, is stabilized by a large number of hydrophobic contacts in the inner region, by 16 long-time persistent hydrogen bonds and by eight salt bridges. The final model, submitted to PDBePISA [39], received the maximum CSS score of 1.0, suggesting that also the hybrid dimer of dimers could have a role in the aggregation [42].…”
Section: Hybrid Dimer Of Dimersmentioning
confidence: 99%